Application of precautionary principle in international trade law and international environmental law: A comparative assessment - Ansari, Abdul Haseeb; Sri , Wartini (Emerald Group Publishing Limited, 2014)
Purpose – The purpose of writing this paper is to present a comparative but critical assessment of the applicability of the precautionary principle (PP) under the SPS Agreement, which is a part of the WTO regime by implication, and under the Cartagena Protocol, which has been made under the Convention on Biological Diversity. Design/methodology/approach – The paper presents an analytical exposition of both the sets of laws, trade law and environmental law. The methodology adopted is library based. The approach is to bring about an amicable co-existence of both the laws so that they could serve the dual purpose, i.e. promotion of trade and protection of “human, animal and plant life and health” and conservation of the environment. Findings – The DSB of the WTO should give due importance to the PP and should apply it liberally, keeping also in view the environmental aspects, so that along with free trade human, animal and plant health and life, and conservation of the environment are also protected. Practical implications – It will change the present paradigm and will bring both the sets of laws together. Originality/value – It focuses on the life and heath of poor people around the world. It, thus, pleads for application of strong PP.